ACR BI‐RADS Category 3 Lesions in Women Younger Than 30: Follow‐up Outcomes and Factors Associated With Biopsy. (18th February 2021) - Merchant, Kanwal; Omar, Lena; Hayes, Jody; Compton, Lindsay; Polat, Dogan; Xi, Yin; Dogan, Basak
Abstract : Objective: Investigate imaging follow‐up patterns and assessment of malignancy rate of BI‐RADS 3 lesions in women younger than 30 years. Methods: We retrospectively reviewed consecutive studies between January 1, 2013 and January 1, 2015 with BI‐RADS 3 assessment in women <30 years. Lesion size, follow‐up rate, and biopsy rate were recorded. Completion of 24‐month imaging follow‐up or biopsy determined the endpoint. Statistical analysis of follow‐up rates and biopsy timing was performed. Results: Of 2525 BI‐RADS 3 lesions, 278 were identified in 215 women <30 years. Fifty‐two (24%) women underwent a biopsy which was more frequently done at patient request than for lesion growth [33 (63.4%) versus 19 (36.5%), P <.01]. The odds of having biopsy upfront was significantly higher in lesions >2 cm in diameter (OR: 4.4 [95% CI 2.1–9.4], P <.01). The malignancy rate in our cohort was 0% (95% CI 0–1.7%). Of the 188 women expected for follow‐up imaging, 58 (30%) were lost to follow‐up, while 103 (55%) had 6‐month follow‐up, 74 (39%) 12‐month follow‐up, and 56 (30%) 24‐month follow‐up. Conclusions: BI‐RADS 3 lesions identified in our cohort had high biopsy rates and low compliance with no cancers. Our findings suggest that probable fibroadenomas in young women may only warrant abbreviated short‐term follow‐up at 6‐months. Abstract : Access the CME test here and search by article title.